Assessment of Waldeyer's ring in pediatric and adolescent Hodgkin lymphoma patients—Importance of multimodality imaging: Results from the EuroNet‐PHL‐C1 trial. Issue 4 (3rd February 2021) - Kurch, Lars; Mauz‐Körholz, Christine; Fosså, Alexander; Georgi, Thomas Walther; Kluge, Regine; Bartelt, Jörg Martin; Kunze, Christian; Wohlgemuth, Walter Alexander; Pelz, Tanja; Vordermark, Dirk; Plößl, Sebastian; Hasenclever, Dirk; et al.
Abstract: Background: In the EuroNet Pediatric Hodgkin Lymphoma (EuroNet‐PHL) trials, decision on Waldeyer's ring (WR) involvement is usually based on clinical assessment, that is, physical examination and/or nasopharyngoscopy. However, clinical assessment only evaluates mucosal surface and is prone to interobserver variability. Modern cross‐sectional imaging technology may provide valuable information beyond mucosal surface, which may lead to a more accurate WR staging. Patients, materials, and methods: The EuroNet‐PHL‐C1 trial recruited 2102 patients, of which 1752 underwent central review including reference reading of their cross‐sectional imaging data. In 14 of 1752 patients, WR was considered involved according to clinical assessment. In these 14 patients, the WR was re‐assessed by applying an imaging‐based algorithm considering information from 18 F‐fluorodeoxyglucose positron emission tomography, contrast‐enhanced computed tomography, and/or magnetic resonance imaging. For verification purposes, the imaging‐based algorithm was applied to 100 consecutive patients whose WR was inconspicuous on clinical assessment. Results: The imaging‐based algorithm confirmed WR involvement only in four of the 14 patients. Of the remaining 10 patients, four had retropharyngeal lymph node involvement and six an inconspicuous WR. Applying the imaging‐based algorithm to 100 consecutive patients with physiological appearance of their WR on clinical assessment, absence of WR involvement could be confirmed in 99. However, suspicion of WR involvement was raised in one patient. Conclusions: The imaging‐based algorithm was feasible and easily applicable at initial staging of young patients with Hodgkin lymphoma. It increased the accuracy of WR staging, which may contribute to a more individualized treatment in the future.